2014
DOI: 10.5863/1551-6776-19.3.165
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of a Pharmacist-Managed, Neonatal and Pediatric, Opioid-Weaning Protocol

Abstract: OBJECTIVES: To compare the length of wean and abstinence severity in neonatal and pediatric patients with neonatal abstinence syndrome or iatrogenic opioid dependence treated with a pharmacist-managed, methadone-based protocol compared with physician-managed patients treated with either methadone or dilute tincture of opium (DTO). METHODS: This was a prospective, single-centered, interventional evaluation of 54 pharmacist-managed patients versus 53 retrospective, physician-managed patients. Wean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(42 citation statements)
references
References 21 publications
0
42
0
Order By: Relevance
“…Steineck et al 14 showed similar results in their study; a pharmacist-managed methadone taper reduced the average taper length from 24.7 days to 15 days. However, research by Johnson et al 17 did not find a difference in taper length between pharmacist-managed and physician-managed children with methadone use for iatrogenic opioid withdrawal, although pharmacist-managed patients had fewer elevated withdrawal scores. 17 Additionally, Abdouni et al 25 reported a reduction in methadone taper length from 15.3 days to 9.5 days with the use of a standardized withdrawal guideline, though this was not a pharmacist-managed protocol.…”
Section: Discussionmentioning
confidence: 90%
“…Steineck et al 14 showed similar results in their study; a pharmacist-managed methadone taper reduced the average taper length from 24.7 days to 15 days. However, research by Johnson et al 17 did not find a difference in taper length between pharmacist-managed and physician-managed children with methadone use for iatrogenic opioid withdrawal, although pharmacist-managed patients had fewer elevated withdrawal scores. 17 Additionally, Abdouni et al 25 reported a reduction in methadone taper length from 15.3 days to 9.5 days with the use of a standardized withdrawal guideline, though this was not a pharmacist-managed protocol.…”
Section: Discussionmentioning
confidence: 90%
“…Of the 13 studies, 10 were NRSI [31][32][33][34][35][36][37][38][39][40], and 3 were randomised controlled trials (RCTs) [41][42][43] (Table 1). Nine studies were conducted in North American ICUs [31,33,34,[37][38][39][40][41][42] and 12 were single-centre studies [43].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Heterogeneity was found in the type of patients included (Table 1). Only two studies involved adult patients [35,43], while the rest involved neonatal and paediatric patients [31][32][33][34][36][37][38][39][40][41][42]. Nine studies included only patients at risk of IWS based on opioid and/or benzodiazepine exposure of at least 5 days in six studies [32,33,[40][41][42][43] and at least 7 days in three studies [31,37,38].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations